So you're a teenager : vital facts for boys - Knight, John F. (Victoria : Signs Publishing Co., 1994)
Dr. Knight is well-known on television and radio in Australia. He goes over what happens when boys enter puberty, sexual intercourse, hormones, dieting, drugs and sexually transmitted diseases
Includes index
Keywords: Sex education for boys; Conduct of life -- Boys; Adolescence -- Boys